(untitled) (Research, Society and Development, 2021)
Introduction: The use of technologies is increasingly changing, while also changing people. Contact with current technologies, such as smartphones, can generate several emotional responses and alter subjective well-being, one of which is nomophobia. Objective: To analyze the population’s interactivity with smartphones, with the objective of verifying the impact caused on the quality of life and the development of nomophobia. Methods: The sample consisted of 96 smartphone users who answered a set of questions based on the form: questionnaire for assessing smartphone dependency (Khoury, 2017) that addressed statements related to cell phone dependency. Affirmations could be answered in a positive or negative way. The data were carried out using a quantitative and statistical descriptive method. Results and discussion: It was discovered that 90.6% (87) of the sample is composed of young people between 14 and 20 years old and 62.5% (60) of the female gender. Among women, 53.3% (32) obtained a positive score for the tendency to nomophobia. Despite the symptoms of anxiety and dependence not yet manifesting in most participants, it was observed in 65.6% (63) of the sample that some attitudes are already evident, such as looking at messages or applications continuously, waiting for some recent social interaction. Conclusion: It was identified that the excessive use of electronic devices capable of accessing the internet is the main factor for the development of nomophobia, interfering negatively in the quality of life of qualified people. Among them, the youngest, with more access to the internet, are more likely to present clinical manifestations of nomophobia.